2009
DOI: 10.1007/s10340-009-0265-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of botanical insecticide Nimbecidine® on food consumption and egg hatchability of the terrestrial snail Monacha obstructa

Abstract: In the laboratory, a commercial neem-based insecticide-Nimbecidine ® -was evaluated as a potential pest management tool for the terrestrial snail, Monacha obstructa (PfeiVer, 1842) (Hygromiidae). EVects of diVerent concentrations of the botanical insecticide on food consumption and egg hatchability of the terrestrial snail were studied. Generally, food consumption of immature and adult snails decreased as the concentrations of Nimbecidine ® increased. At the highest concentration (10 ml/l), the snails avoided … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 22 publications
0
3
0
1
Order By: Relevance
“…Neem ağacı (Azadirachta indica, Meliaceae)'ndan elde edilmiş olan Azadirachtin pek çok zararlı böceğe karşı öldürücü, beslenmeyi ve büyümeyi engelleyici olarak kullanılmaktadır (Charleston et al 2006;Göçmen et al 2007;Schneider et al 2017). Azadiracthin etkili maddeli preparatların yaprak bitleri başta olmak üzere bazı zararlıların popülasyonunu kontrol altında tutabildiği yapılan çalışmalarda bildirilmiştir (Shoaib et al 2010;El-Salam et al 2012;Bhardwaj & Ansari, 2015). Bu çalışmada da kullanılan Azadirachtin etkili maddeli (Nimbecidine) preparatın yaprak bitleri üzerinde yüksek lethal etki gösterebildiği saptanmıştır.…”
Section: İstatistiksel Analizlerunclassified
“…Neem ağacı (Azadirachta indica, Meliaceae)'ndan elde edilmiş olan Azadirachtin pek çok zararlı böceğe karşı öldürücü, beslenmeyi ve büyümeyi engelleyici olarak kullanılmaktadır (Charleston et al 2006;Göçmen et al 2007;Schneider et al 2017). Azadiracthin etkili maddeli preparatların yaprak bitleri başta olmak üzere bazı zararlıların popülasyonunu kontrol altında tutabildiği yapılan çalışmalarda bildirilmiştir (Shoaib et al 2010;El-Salam et al 2012;Bhardwaj & Ansari, 2015). Bu çalışmada da kullanılan Azadirachtin etkili maddeli (Nimbecidine) preparatın yaprak bitleri üzerinde yüksek lethal etki gösterebildiği saptanmıştır.…”
Section: İstatistiksel Analizlerunclassified
“…In soil ecotoxicology with invertebrates, embryonic development tests are limited (Druart et al, 2010). A few studies were performed using the terrestrial slugs Deroceras reticulatum (Iglesias et al, 2002(Iglesias et al, , 2000 and snails Monacha obstructa (Shoaib et al, 2010) to assess embryotoxic effects of metals and pesticides and for Helix aspersa (syn. Cantareus aspersus) an embryotoxicity test has been proposed (Baurand et al, 2014;Druart et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it was also reported that plant metabolites were acknowledged as protection against snails [ 23 , 24 ]. More than 1500 species of plants had been evaluated for potential molluscicidal activity, and most of them are the family of Theaceae , Meliaceae , Apocynaceae , Euphorbiaceae , Leguminosae , Phytolaccaceae , Solanaceae, and Rutaceae [ 25 ].…”
Section: Introductionmentioning
confidence: 99%